Conductive filler and preparation method thereof, conductive adhesive and electronic equipment

The conductive copolymer layer formed by polyethylene glycol and polyaniline is coated with nickel-clad graphite powder, which solves the problem of degradation of the conductivity of traditional nickel-clad graphite powder, and realizes the high conductivity and weather resistance of the conductive glue, satisfying the 5G base station Harsh requirements.

CN119286426APending Publication Date: 2025-01-10BGRIMM ADVANCED MATERIALS SCI & TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411425400.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The nickel oxide layer formed by traditional nickel-clad graphite powder in the hydrogen reduction process leads to a decrease in conductivity. The existing modification treatment effect is not ideal, making it difficult to meet the high conductivity requirements of 5G base stations for conductive glue.

Method used

The conductive copolymer layer formed by polyethylene glycol and polyaniline is coated with nickel-covered graphite powder. The affinity and binding force of the nickel surface are improved through mechanisms such as hydrogen bonding, chemical bonding, interface interaction and conductivity, and the conductive filler is formed. .

Benefits of technology

It significantly improves the conductive performance, optimizes the conductive performance of the conductive glue, adapts to the high temperature and high humidity environment of 5G base stations, and ensures stable signal transmission and long-term reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286426A_ABST
    Figure CN119286426A_ABST
Patent Text Reader

Abstract

The invention provides a conductive filler and a preparation method thereof, a conductive adhesive and electronic equipment, and relates to the field of conductive materials. The conductive filler comprises nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder; the conductive copolymer layer comprises a block copolymer formed by polyethylene glycol and polyaniline. The conductive copolymer layer formed by polyethylene glycol and polyaniline can improve the affinity between the conductive copolymer layer and the nickel surface and improve the binding force between polyaniline and nickel, thereby improving the conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of conductive materials, and in particular to a conductive filler and a preparation method thereof, a conductive adhesive and an electronic device. Background Art

[0002] With the rapid development of 5G communication technology and the large-scale construction of 5G base stations, higher requirements are placed on the conductivity of electronic equipment. As an important conductive component in electronic equipment, the conductivity of conductive adhesive directly affects the performance of the entire circuit system. As a key filler in conductive adhesive, the conductivity of nickel-coated graphite powder plays a decisive role in the conductivity of conductive adhesive.

[0003] Traditional nickel-coated graphite powder is usually prepared by a hydrogen reduction process. During the reduction process, the surface of the nickel coating will undergo a certain degree of oxidation to form an insulating nickel oxide layer. The presence of the nickel oxide layer will increase the contact resistance between the nickel particles and the graphite matrix, affecting the smooth flow of electrons between the two, thereby causing a decrease in the overall conductivity. The nickel oxide layer will also form an insulating isolation film on the surface of the nickel particles, which will block the electron transmission path and cause a decrease in the overall conductivity.

[0004] To solve the above problems, researchers have tried various modification treatments on the surface of nickel-coated graphite powder, such as coating metal oxides, silicone compounds, etc., but the modification effect is often not ideal and it is difficult to meet the requirements of 5G base station conductive adhesives. Summary of the invention

[0005] The purpose of the present application is to provide a conductive filler and a preparation method thereof, a conductive adhesive and an electronic device to solve the above problems.

[0006] To achieve the above objectives, the present application provides a conductive filler in a first aspect, comprising nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder;

[0007] The conductive copolymer layer includes a block copolymer formed by polyethylene glycol and polyaniline.

[0008] Optionally, the conductive filler satisfies at least one of the following conditions:

[0009] A. The Ni content of the nickel-coated graphite powder is 58%-62% of the total mass, and the C content is 38%-42% of the total mass;

[0010] B. The thickness of the conductive copolymer layer is 1 μm-5 μm;

[0011] C. The particle size of the conductive filler is minus 140 mesh to minus 325 mesh;

[0012] D. The mass ratio of the polyethylene glycol to the polyaniline is 1:(8-15).

[0013] The second aspect of the present application provides a method for preparing the conductive filler, comprising:

[0014] The polyethylene glycol, the polyaniline and the organic solvent are first mixed to obtain a conductive copolymer mixed solution;

[0015] The conductive copolymer mixed solution and the nickel-coated graphite powder are subjected to fluidized bed coating and drying to obtain the conductive filler.

[0016] Optionally, the method for preparing the conductive filler satisfies at least one of the following conditions:

[0017] A. Under a reducing atmosphere, the nickel-coated graphite powder is pretreated to obtain treated nickel-coated graphite powder, and the treated nickel-coated graphite powder is subjected to fluidized bed coating;

[0018] B. The concentration of the conductive copolymer mixed solution is 2%-5.5%.

[0019] Optionally, the method for preparing the conductive filler satisfies at least one of the following conditions:

[0020] A. The gas in the reducing atmosphere includes hydrogen;

[0021] B. The pretreatment temperature is 500°C-600°C, and the insulation time is 2h-4h.

[0022] Optionally, the fluidized bed coating comprises:

[0023] The nickel-coated graphite powder is dispersed;

[0024] The conductive copolymer mixed solution is sprayed on the surface of the dispersed nickel-coated graphite powder.

[0025] Optionally, the method for preparing the conductive filler satisfies at least one of the following conditions:

[0026] A. The dispersed air inlet temperature is 90°C-110°C;

[0027] B. The dispersed air inlet pressure is 1.0 bar-1.5 bar;

[0028] C. The dispersed air flow rate is 5m 3 / h-10m 3 / h;

[0029] D. The spray pressure of the spraying is 0.7 bar-1.5 bar;

[0030] E. The spraying speed of the spraying is 50mL / min-80mL / min;

[0031] F. The atomization time of the spraying is 5min-10min.

[0032] Optionally, the drying temperature is 100°C-120°C, and the drying time is 2h-4h.

[0033] A third aspect of the present application provides a conductive adhesive, comprising the conductive filler described above or a conductive filler prepared by the preparation method of the conductive filler described above.

[0034] A fourth aspect of the present application provides an electronic device, comprising the conductive adhesive.

[0035] Compared with the prior art, the beneficial effects of this application include:

[0036] The conductive filler provided in the present application, the conductive copolymer layer formed by polyethylene glycol (PEG) and polyaniline can improve its affinity with the nickel surface and enhance the binding force between polyaniline and nickel through the combined action of multiple mechanisms such as hydrogen bonding, chemical bonding, interface interaction, wettability and conductivity, as follows: Hydrogen bonding and chemical bonding: the hydroxyl group (-OH) in PEG can form hydrogen bonds with the nickel surface, thereby enhancing the adhesion of the conductive copolymer layer to the nickel surface; the amino group (-NH) and benzene ring in polyaniline can chemically react with the nickel surface to form a metal-polymer chemical bond; Enhanced binding force; interface interaction: the presence of the conductive copolymer layer can form a more complex interface interaction between polyaniline and nickel, including van der Waals forces, hydrogen bonds and electrostatic interactions, all of which can enhance the binding force; wettability and surface energy: the hydrophilic characteristics of PEG improve the wettability of the conductive copolymer layer, making it easier to form a uniform coating on the nickel surface, reducing the surface energy and thus improving the affinity; conductivity: the conductivity of polyaniline enhances the electronic interaction between it and nickel, promotes the transfer of electrons, thereby increasing the binding force and thus improving the conductivity.

[0037] The preparation method of the conductive filler provided in the present application realizes large-scale and continuous coating of nickel-coated graphite powder through fluidized bed coating. The preparation method is simple to operate, has high production efficiency and uniform coating.

[0038] The conductive adhesive and electronic device provided in this application have excellent conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0040] Figure 1is the SEM image of the block copolymer in Example 1;

[0041] Figure 2 is a flow chart of the preparation method of the conductive filler prepared in Example 1;

[0042] Figure 3 This is a surface SEM image of the conductive filler prepared in Example 1;

[0043] Figure 4 This is a cross-sectional SEM image of the conductive filler prepared in Example 1. DETAILED DESCRIPTION

[0044] As used herein:

[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0046] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0047] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0048] In these examples, parts and percentages are by mass unless otherwise indicated.

[0049] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0050] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0051] In a first aspect, the present application provides a conductive filler, comprising nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder;

[0052] The conductive copolymer layer includes a block copolymer formed by polyethylene glycol and polyaniline.

[0053] In some embodiments, the conductive filler satisfies at least one of the following conditions:

[0054] A. The Ni content of the nickel-coated graphite powder is 58%-62% of the total mass, and the C content is 38%-42% of the total mass;

[0055] Optionally, the Ni content in the nickel-coated graphite powder is 58%, 59%, 60%, 61%, 62% or any value between 58% and 62% of the total mass, and the C content is 38%, 39%, 40%, 41%, 42% or any value between 38% and 42% of the total mass;

[0056] B. The thickness of the conductive copolymer layer is 1 μm-5 μm;

[0057] Optionally, the thickness of the conductive copolymer layer may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value between 1 μm and 5 μm;

[0058] It should be noted that the thickness of the conductive copolymer layer is related to the control of the air inlet pressure, air inlet flow rate, spray pressure and spray flow rate. By controlling the above parameters, the thickness of the conductive copolymer layer can be ensured to be in the range of 1μm-5μm; when the thickness of the conductive copolymer layer is less than 1um, it will lead to the inability to form a continuous conductive network, resulting in a decrease in conductivity, affecting the conductivity improvement effect, service life and stability; when the thickness of the conductive copolymer layer is greater than 5μm, it will increase the resistance of electrons when penetrating the film, resulting in an increase in the overall resistance. In addition, the increase in the thickness of the conductive copolymer layer may generate greater internal stress inside the conductive copolymer layer, which will lead to a decrease in the bonding force between the conductive copolymer layer and the nickel-coated graphite powder, thereby affecting the conductivity. Moreover, the increase in the thickness of the conductive copolymer layer will consume more raw materials, thereby increasing production costs.

[0059] C. The particle size of the conductive filler is minus 140 mesh to minus 325 mesh;

[0060] Optionally, the particle size of the conductive filler may be minus 140 mesh, minus 100 mesh, minus 50 mesh, 10 mesh, 50 mesh, 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, 325 mesh, or any value between minus 140 mesh and 325 mesh;

[0061] It should be noted that when the particle size of the conductive filler is within the range of -140 mesh to 325 mesh, it has the best surface area and conductivity. -140 mesh to 325 mesh can ensure the appropriate specific surface area, increase the contact between the block copolymer and the nickel-coated graphite, and effectively improve the conductivity. When the particle size is less than 325 mesh, it may lead to poor fluidity and agglomeration, while when the particle size is greater than 140 mesh, it may affect the coating uniformity and overall conductivity. When the particle size of the conductive filler is within the range of -140 mesh to 325 mesh, it can also avoid processing inconvenience. Good fluidity and dispersibility can be achieved within the range of -140 mesh to 325 mesh, ensuring easy handling and application during processing, and avoiding processing difficulties or material loss caused by improper particle size. When the particle size of the conductive filler is less than 325 mesh, it may cause poor fluidity and agglomeration, while when the particle size is greater than 140 mesh, it may affect the coating uniformity and overall conductivity. When the particle size of the conductive filler is within the range of -140 mesh to 325 mesh, it can also avoid processing inconvenience. Good fluidity and dispersibility can be achieved within the range of -140 mesh to 325 mesh, ensuring easy handling and application during processing, and avoiding processing difficulties or material loss caused by improper particle size. When the particle size is within the range of -140 mesh to 325 mesh, the performance and cost can be balanced. The cost within the range of -140 mesh to 325 mesh is usually moderate, and the processing is easy. At the same time, a good balance can be achieved in terms of conductivity and mechanical strength, which is suitable for large-scale production. When the particle size of the conductive filler is within the range of -140 mesh to 325 mesh, the mechanical strength and stability can be improved. While maintaining good conductivity, the particles within this range can provide sufficient mechanical strength and stability to avoid structural damage or performance degradation in application. In summary, the selection of conductive fillers within the range of -140 mesh to 325 mesh can find the best balance between conductivity, processing convenience, cost and performance, and meet the coating requirements of block copolymers on the surface of nickel-coated graphite powder.

[0062] D. The mass ratio of the polyethylene glycol to the polyaniline is 1:(8-15).

[0063] Optionally, the mass ratio of polyethylene glycol to polyaniline can be 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15 or any value between 1:(8-15).

[0064] It should be noted that when the mass ratio of polyethylene glycol to polyaniline exceeds 1:8, the addition effect of the formed block copolymer is not obvious, and when the mass ratio of polyethylene glycol to polyaniline is lower than 1:15, less block copolymer is generated and the coating effect is poor.

[0065] The third aspect of the present application provides a method for preparing the conductive filler, comprising:

[0066] The polyethylene glycol, the polyaniline and the organic solvent are first mixed to obtain a conductive copolymer mixed solution;

[0067] The conductive copolymer mixed solution and the nickel-coated graphite powder are subjected to fluidized bed coating and drying to obtain the conductive filler.

[0068] In some embodiments, the method for preparing the conductive filler satisfies at least one of the following conditions:

[0069] A. Under a reducing atmosphere, the nickel-coated graphite powder is pretreated to obtain treated nickel-coated graphite powder, and the treated nickel-coated graphite powder is subjected to fluidized bed coating;

[0070] It should be noted that the pretreatment removes the nickel oxide layer on the surface of the nickel-coated graphite powder and improves the surface activity of the nickel-coated graphite powder.

[0071] B. The concentration of the conductive copolymer mixed solution is 2%-5.5%.

[0072] Optionally, the concentration of the conductive copolymer mixed solution may be 2%, 3%, 4%, 5.5% or any value between 2% and 5.5%.

[0073] It should be noted that when the concentration is higher than 5.5%, the thickness of the coating layer is difficult to control; when the concentration is lower than 2%, it will lead to point coating and uneven film.

[0074] In some embodiments, the method for preparing the conductive filler satisfies at least one of the following conditions:

[0075] A. The gas in the reducing atmosphere includes hydrogen;

[0076] B. The pretreatment temperature is 500°C-600°C, and the insulation time is 1h-4h.

[0077] Optionally, the pretreatment temperature may be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C or any value between 500°C and 600°C, and the holding time may be 1h, 2h, 3h, 4h or any value between 1h and 4h;

[0078] It should be noted that, under a hydrogen flowing atmosphere, when the pretreatment temperature is lower than 500°C, the reaction rate is too slow, and when the pretreatment temperature is higher than 600°C, the effect of removing the nickel oxide layer on the surface of the nickel-coated graphite powder is not significantly enhanced and energy is consumed.

[0079] In some embodiments, the fluidized bed coating comprises:

[0080] The nickel-coated graphite powder is dispersed;

[0081] The conductive copolymer mixed solution is sprayed on the surface of the dispersed nickel-coated graphite powder.

[0082] In some embodiments, the method for preparing the conductive filler satisfies at least one of the following conditions:

[0083] A. The dispersed air inlet temperature is 90°C-110°C;

[0084] Optionally, the dispersed air inlet temperature may be 90°C, 95°C, 100°C, 105°C, 110°C or any value between 90°C and 110°C;

[0085] It should be noted that the inlet air temperature of dispersion is to ensure the working temperature in the fluidized bed atomizer during dispersion, which can quickly dry the conductive copolymer mixed solution so that it is coated on the surface of the nickel-coated graphite powder. When the inlet air temperature is too low, the drying is insufficient and the nickel-coated graphite powders will stick together; when the inlet air temperature is too high, the drying speed is too fast, which affects the bonding strength between the conductive copolymer layer and the nickel-coated graphite powder.

[0086] B. The dispersed air inlet pressure is 1.0 bar-1.5 bar;

[0087] Optionally, the dispersed air inlet pressure may be 1.0 bar, 1.1 bar, 1.2 bar, 1.3 bar, 1.4 bar, 1.5 bar or any value between 1.0 bar and 1.5 bar;

[0088] C. The dispersed air flow rate is 5m 3 / h-10m 3 / h;

[0089] Optionally, the dispersed air flow rate can be 5m 3 / h、6m3 / h、7m 3 / h、8m 3 / h、9m 3 / h、10m 3 / h or 5m 3 / h-10m 3 Any value between / h;

[0090] It should be noted that the dispersed air inlet pressure and air flow rate are to ensure that the nickel-coated graphite powder can be fully dispersed in the fluidized bed atomization tank. When the air inlet pressure is too low, the nickel-coated graphite powder is not blown high enough and cannot be fully dispersed; when the air inlet pressure is too high, the nickel-coated graphite powder is dispersed too quickly and will be blown onto the inner wall of the fluidized bed atomization tank, affecting the coating efficiency and uniformity of the conductive copolymer layer.

[0091] D. The spray pressure of the spraying is 0.7 bar-1.5 bar;

[0092] Optionally, the spray pressure of the spraying may be 0.7 bar, 0.8 bar, 0.9 bar, 1.0 bar, 1.1 bar, 1.2 bar, 1.3 bar, 1.4 bar, 1.5 bar or any value between 0.7 bar and 1.5 bar;

[0093] E. The spraying speed of the spraying is 50mL / min-80mL / min;

[0094] Optionally, the spraying speed of the spraying can be 50mL / min, 55mL / min, 60mL / min, 65mL / min, 70mL / min, 75mL / min, 80mL / min or any value between 50mL / min and 80mL / min;

[0095] It should be noted that the air inlet pressure and spray speed of the spraying are to ensure the atomization speed and film uniformity of the conductive copolymer mixed solution; when the spraying pressure is too low, when the atomization speed of the conductive copolymer mixed solution is low, resulting in a low height of the conductive copolymer mixed solution, it will reduce the uniformity and efficiency of the coating; when the atomization speed is too high, the conductive copolymer mixed solution is discontinuous, resulting in uneven coating.

[0096] F. The atomization time of the spraying is 5min-10min.

[0097] Optionally, the atomization time of the spraying can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or any value between 5 min and 10 min.

[0098] In some embodiments, the drying temperature is 100° C.-120° C., and the drying time is 2 h-4 h.

[0099] Optionally, the drying temperature may be 100°C, 105°C, 110°C, 115°C, 120°C or any value between 100°C and 120°C, and the drying time may be 2h, 3h, 4h or any value between 2h and 4h.

[0100] It should be noted that the purpose of drying is to remove residual solvents, in some embodiments, to remove organic solvents; illustratively, to remove ethanol.

[0101] A third aspect of the present application provides a conductive adhesive, comprising the conductive filler described above or a conductive filler prepared by the preparation method of the conductive filler described above.

[0102] It should be noted that 5G base stations have stringent requirements for conductive properties. The special requirements faced by 5G base station conductive adhesives include high conductivity, high temperature and weather resistance, good adhesion, low thermal expansion coefficient, and anti-electromagnetic interference to ensure stable signal transmission and long-term reliability. However, conductive adhesives in existing technologies usually rely on metal powders or carbon-based materials as fillers. These materials may cause signal attenuation in high-frequency applications and are prone to performance degradation in extreme environments. In addition, the processing technology and cost limitations of existing conductive adhesives also make it difficult to meet the strict requirements of 5G base stations for conductive adhesives.

[0103] A fourth aspect of the present application provides an electronic device, comprising the conductive adhesive.

[0104] It should be noted that conventional conductive adhesives are often difficult to meet these requirements due to oxidation of conductive fillers, insufficient bonding strength and poor environmental adaptability. In contrast, the conductive filler provided in the present application is coated with a block copolymer formed by polyethylene glycol and polyaniline. With its excellent conductive properties, good thermal stability and enhanced adhesion, it can effectively cope with harsh environments such as high temperature and high humidity, and ensure the long-term stable operation of 5G base stations.

[0105] It should also be noted that the electronic device can be one or more of a heat sink, a PCB (printed circuit board), a temperature sensor, a humidity sensor, and a radio frequency module in a 5G base station.

[0106] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0107] The nickel-coated graphite powder used in the embodiments of the present application is a homemade nickel-coated graphite powder, and the preparation method includes:

[0108] Water, a buffer, nickel sulfate, ammonia water, artificial graphite, anthraquinone, a reducing agent and an activating agent are mixed to obtain a mixed material; the mixed material is heated, and hydrogen is introduced to react to obtain a reaction product; the reaction product is washed and dried to obtain nickel-coated graphite powder.

[0109] The buffer comprises ammonium sulfate; the reducing agent comprises hydrazine hydrate; the active agent comprises polyethylene glycol PEG 600; the heating temperature is 120° C.-150° C., the reaction time is 3 h-4 h, and the reaction device comprises a 20 L vertical high-pressure reactor.

[0110] The preparation method of the conductive filler provided in the present application can also use purchased nickel-coated graphite powder.

[0111] Example 1

[0112] A first aspect of the present embodiment provides a conductive filler, comprising nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder, wherein the conductive copolymer layer comprises a block copolymer formed by polyethylene glycol and polyaniline, wherein the mass ratio of polyethylene glycol to the polyaniline is 1:10, the Ni content in the nickel-coated graphite powder is 60% of the total mass, the C content is 40% of the total mass, the thickness of the conductive copolymer layer is 1.5 μm, and the particle size of the conductive filler is negative 140 mesh-325 mesh.

[0113] The SEM images of the block copolymers are shown in Figure 1 shown.

[0114] A second aspect of the present embodiment provides a method for preparing a conductive filler, comprising:

[0115] S1. Preparation of a conductive copolymer mixed solution: 1 kg of soluble polyaniline powder, 0.1 kg of polyethylene glycol, and 48.9 kg of ethanol were mixed, and the mixture was stirred at a speed of 50 r / min for 30 min to prepare a conductive copolymer mixed solution with a concentration of 2%;

[0116] S2. Pretreatment of nickel-coated graphite powder: The nickel-coated graphite powder prepared by hydrogen reduction process is added into a debonding and sintering integrated furnace after washing and drying. Under hydrogen atmosphere, the reduction temperature is set to 500° C. and the holding time is 3 h to obtain the treated nickel-coated graphite powder;

[0117] S3, fluidized bed coating: put the treated nickel-coated graphite powder into the fluidized bed spraying device, set the inlet air temperature to 90 ° C, the inlet air pressure to 1 bar, and the flow rate to 5m 3 / h, the nickel-coated graphite powder is evenly dispersed in the device through the action of the fluidized bed; the conductive copolymer mixed solution is added to the fluidized bed atomization tank through an infusion pump, the spray speed is set to 50mL / min, the pressure is 0.7bar, and the atomization time is 10min, and the conductive copolymer mixed solution is evenly sprayed on the surface of the nickel-coated graphite powder through a spraying device;

[0118] S4, drying: putting the material prepared in S3 into an oven, setting the temperature to 100° C., and drying for 4 hours to obtain a conductive filler.

[0119] The preparation method of the conductive filler is as follows: Figure 2 shown.

[0120] The surface SEM of the conductive filler is shown in Figure 3 shown.

[0121] The cross-sectional SEM of the conductive filler is shown in FIG. Figure 4 shown.

[0122] A third aspect of this embodiment provides a 5G base station conductive adhesive, including the conductive filler prepared as described above.

[0123] A fourth aspect of this embodiment provides an electronic device PCB (printed circuit board), including 5G base station conductive adhesive.

[0124] Example 2

[0125] A first aspect of the present embodiment provides a conductive filler, comprising nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder, wherein the conductive copolymer layer comprises a block copolymer formed by polyethylene glycol and polyaniline, wherein the mass ratio of polyethylene glycol to the polyaniline is 1:10, the Ni content in the nickel-coated graphite powder is 60% of the total mass, the C content is 40% of the total mass, the thickness of the conductive copolymer layer is 3.6 μm, and the particle size of the conductive filler is negative 140 mesh-325 mesh.

[0126] A second aspect of the present embodiment provides a method for preparing a conductive filler, comprising:

[0127] S1. Preparation of a conductive copolymer mixed solution: 1 kg of soluble polyaniline powder, 0.1 kg of polyethylene glycol, and 18.9 kg of ethanol were mixed, and the mixture was stirred at a speed of 50 r / min for 30 min to prepare a conductive copolymer mixed solution with a concentration of 5%;

[0128] S2. Pretreatment of nickel-coated graphite powder: The nickel-coated graphite powder prepared by hydrogen reduction process is added into a debonding and sintering integrated furnace after washing and drying. Under hydrogen atmosphere, the reduction temperature is set to 600° C. and the holding time is 1 h to obtain the treated nickel-coated graphite powder;

[0129] S3, fluidized bed coating: put the treated nickel-coated graphite powder into the fluidized bed spraying device, set the inlet air temperature to 100℃, the inlet air pressure to 1.5bar, and the flow rate to 7m 3 / h, the nickel-coated graphite powder is evenly dispersed in the device through the action of the fluidized bed; the conductive copolymer mixed solution is added to the fluidized bed atomization tank through an infusion pump, the spray speed is set to 70mL / min, the pressure is 1.0bar, and the atomization time is 7min, and the conductive copolymer mixed solution is evenly sprayed on the surface of the nickel-coated graphite powder through a spraying device;

[0130] S4, drying: putting the material prepared in S3 into an oven, setting the temperature to 120° C., and drying for 2 h to obtain a conductive filler.

[0131] Example 3

[0132] A first aspect of the present embodiment provides a conductive filler, comprising nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder, wherein the conductive copolymer layer comprises a block copolymer formed by polyethylene glycol and polyaniline, wherein the mass ratio of polyethylene glycol to the polyaniline is 1:10, the Ni content in the nickel-coated graphite powder is 60% of the total mass, the C content is 40% of the total mass, the thickness of the conductive copolymer layer is 4.8 μm, and the particle size of the conductive filler is negative 140 mesh-325 mesh.

[0133] A second aspect of the present embodiment provides a method for preparing a conductive filler, comprising:

[0134] S1. Preparation of a conductive copolymer mixed solution: 1 kg of soluble polyaniline powder, 0.1 kg of polyethylene glycol, and 38.9 kg of ethanol were mixed, and the mixture was stirred at a speed of 60 r / min for 60 min to prepare a conductive copolymer mixed solution with a concentration of 2.5%;

[0135] S2. Pretreatment of nickel-coated graphite powder: The nickel-coated graphite powder prepared by hydrogen reduction process is added into a debonding and sintering integrated furnace after washing and drying. Under hydrogen atmosphere, the reduction temperature is set to 540° C. and the holding time is 2.5 h to obtain the treated nickel-coated graphite powder;

[0136] S3, fluidized bed coating: put the treated nickel-coated graphite powder into the fluidized bed spraying device, set the inlet air temperature to 110℃, the inlet air pressure to 1.2bar, and the flow rate to 10m 3 / h, the nickel-coated graphite powder is evenly dispersed in the device through the action of the fluidized bed; the conductive copolymer mixed solution is added to the fluidized bed atomizer tank through an infusion pump, the spray speed is set to 80mL / min, the pressure is 1.5bar, and the atomization time is 5min, and the conductive copolymer mixed solution is evenly sprayed on the surface of the nickel-coated graphite powder through a spraying device;

[0137] S4, drying: putting the material prepared in S3 into an oven, setting the temperature to 110° C., and drying for 3 hours to obtain a conductive filler.

[0138] Example 4

[0139] A first aspect of the present embodiment provides a conductive filler, comprising nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder, wherein the conductive copolymer layer comprises a block copolymer formed by polyethylene glycol and polyaniline, wherein the mass ratio of polyethylene glycol to the polyaniline is 1:10, the Ni content in the nickel-coated graphite powder is 60% of the total mass, the C content is 40% of the total mass, the thickness of the conductive copolymer layer is 2.4 μm, and the particle size of the conductive filler is negative 140 mesh-325 mesh.

[0140] A second aspect of the present embodiment provides a method for preparing a conductive filler, comprising:

[0141] S1. Preparation of a conductive copolymer mixed solution: 1 kg of soluble polyaniline powder, 0.1 kg of polyethylene glycol, and 28.9 kg of ethanol were mixed at a stirring speed of 100 r / min for 50 min to prepare a conductive copolymer mixed solution with a concentration of 3.3%;

[0142] S2. Pretreatment of nickel-coated graphite powder: The nickel-coated graphite powder prepared by hydrogen reduction process is added into a debonding and sintering integrated furnace after washing and drying. Under hydrogen atmosphere, the reduction temperature is set to 580° C. and the holding time is 1.5 h to obtain the treated nickel-coated graphite powder;

[0143] S3, fluidized bed coating: put the treated nickel-coated graphite powder into the fluidized bed spraying device, set the inlet air temperature to 95 ° C, the inlet air pressure to 1.4 bar, and the flow rate to 8m 3 / h, the nickel-coated graphite powder is evenly dispersed in the device through the action of the fluidized bed; the conductive copolymer mixed solution is added to the fluidized bed atomizer tank through the infusion pump, the spray speed is set to 60mL / min, the pressure is 1.2bar, and the atomization time is 8min, and the conductive copolymer mixed solution is evenly sprayed on the surface of the nickel-coated graphite powder through the spraying device;

[0144] S4, drying: putting the material prepared in S3 into an oven, setting the temperature to 115° C., and drying for 2.5 h to obtain a conductive filler.

[0145] Comparative Example 1

[0146] This comparative example provides a conductive filler and a preparation method thereof, which is different from Example 1 in that the raw material of the conductive copolymer layer of this comparative example is only polyaniline, and other conditions are consistent with Example 1.

[0147] Comparative Example 2

[0148] This comparative example provides a conductive filler and a preparation method thereof. The difference from Example 1 is that the conductive copolymer layer of this comparative example is only polyethylene glycol, and other conditions are consistent with Example 1.

[0149] Comparative Example 3

[0150] In a first aspect, this comparative example provides a conductive filler, which is different from Example 1 in that the thickness of the conductive copolymer layer in this comparative example is 7.5 μm, and other conditions are consistent with those in Example 1.

[0151] The second aspect of this comparative example provides a method for preparing a conductive filler, which is different from Example 1 in that the atomization time in the S3 fluidized bed coating step of this comparative example is 15 minutes, and other conditions are consistent with Example 1.

[0152] Comparative Example 4

[0153] In a first aspect, this comparative example provides a conductive filler, which is different from Example 1 in that the thickness of the conductive copolymer layer in this comparative example is 0.8 μm, and other conditions are consistent with those in Example 1.

[0154] The second aspect of this comparative example provides a method for preparing a conductive filler, which is different from Example 1 in that the atomization time in the S3 fluidized bed coating step of this comparative example is 3 minutes, and other conditions are consistent with Example 1.

[0155] Comparative Example 5

[0156] In a first aspect, this comparative example provides a conductive filler, which is different from Example 1 in that the thickness of the conductive copolymer layer in this comparative example is 22 μm, and other conditions are consistent with those in Example 1.

[0157] The second aspect of this comparative example provides a method for preparing a conductive filler, which is different from Example 1 in that this comparative example adopts agglomeration granulation coating in S3, and other conditions are consistent with Example 1.

[0158] Comparative Example 6

[0159] This comparative example provides a method for preparing a conductive filler, which is different from Example 1 in that in step S3 of this comparative example, the treated nickel-coated graphite powder is placed in a fluidized bed spraying device, and the inlet air temperature is set to 80°C, the inlet air pressure is set to 1.8 bar, and the flow rate is 12 m 3 / h, the nickel-coated graphite powder is evenly dispersed in the device through the action of the fluidized bed; the conductive copolymer mixed solution is added to the fluidized bed atomization tank through an infusion pump, the spray speed is set to 100mL / min, the pressure is 1.8bar, and the atomization time is 4min, and the conductive copolymer mixed solution is evenly sprayed on the surface of the nickel-coated graphite powder through a spraying device; other conditions are consistent with Example 1.

[0160] Comparative Example 7

[0161] This comparative example provides a method for preparing a conductive filler, which is different from Example 1 in that no pretreatment is performed in this comparative example, and other conditions are consistent with those in Example 1.

[0162] The conductive fillers prepared in the above examples and comparative examples were tested for volume resistivity, and the specific results are shown in Table 1.

[0163] Volume resistivity test method: four-probe method.

[0164] Table 1 Volume resistivity test

[0165] sample Volume resistivity(Ωcm) Example 1 <![CDATA[1.22×10 -5 <!-- 9 -->]]> Example 2 <![CDATA[1.24×10 -5 ]]> Example 3 <![CDATA[1.23×10 -5 ]]> Example 4 <![CDATA[1.25×10 -5 ]]> Comparative Example 1 Polyaniline is insoluble in alcohol and cannot be implemented Comparative Example 2 <![CDATA[3.93×10 -5 ]]> Comparative Example 3 <![CDATA[5.87×10 -5 ]]> Comparative Example 4 <![CDATA[4.12×10 -5 ]]> Comparative Example 5 <![CDATA[6.36×10 -4 ]]> Comparative Example 6 <![CDATA[4.45×10 -5 ]]> Comparative Example 7 <![CDATA[5.52×10 -5 ]]>

[0166] As shown in Table 1, since polyaniline is insoluble in alcohol in Comparative Example 1, the volume resistivity of Comparative Example 1 cannot be tested;

[0167] In Comparative Example 2, only polyethylene glycol was added without polyaniline, and a conductive copolymer could not be formed, and the volume resistivity of the prepared conductive filler increased significantly;

[0168] In Comparative Example 3, the thickness of the conductive copolymer layer formed on the surface of the conductive filler is greater than 5 μm. When it reaches 7.5 μm, the barrier for electrons to penetrate the film is increased, resulting in an increase in the overall resistance. In addition, the increase in the thickness of the conductive copolymer layer may generate greater internal stress inside the conductive copolymer layer, which will cause the bonding force between the conductive copolymer layer and the nickel-coated graphite powder to decrease, thereby affecting the conductive performance and significantly increasing the volume resistivity.

[0169] In Comparative Example 4, the thickness of the conductive copolymer layer formed on the surface of the conductive filler is less than 1 μm. When it reaches 0.8 μm, the volume resistivity increases significantly. This is because when the thickness of the conductive copolymer layer is less than 1 μm, a continuous conductive network cannot be formed, resulting in a decrease in the conductive performance and affecting the conductivity improvement effect.

[0170] Comparative Example 5 adopts agglomeration granulation coating process. Since the thickness of the conductive copolymer layer cannot be accurately controlled by this process, its thickness reaches 22 μm, and the volume resistivity increases significantly;

[0171] When the relevant parameters during fluidized bed coating in Comparative Example 6 do not meet the parameters specified in the present application, the surface of the obtained conductive filler cannot be dried to form a uniform conductive copolymer layer, and the volume resistivity increases significantly;

[0172] In Comparative Example 7, no pretreatment was performed, and the volume resistivity of the conductive filler was significantly increased. This is because the nickel oxide layer on the surface of the nickel-coated graphite powder will reduce the electron transfer efficiency between polyaniline and nickel, which is not conducive to interfacial electrical coupling, resulting in a decrease in the conductivity between polyaniline and nickel; in addition, the surface affinity of the nickel oxide layer is poor, and the combination with polyaniline with stronger affinity is weak, which will affect the physical adsorption and mechanical locking between the interfaces, resulting in a significant increase in the volume resistivity.

[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0174] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A conductive filler, characterized in that: It comprises nickel-coated graphite powder and a conductive copolymer layer coating the nickel-coated graphite powder; The conductive copolymer layer includes a block copolymer formed by polyethylene glycol and polyaniline.

2. The conductive filler according to claim 1, characterized in that: At least one of the following conditions is met: A. The Ni content of the nickel-coated graphite powder is 58%-62% of the total mass, and the C content is 38%-42% of the total mass; B. The thickness of the conductive copolymer layer is 1 μm-5 μm; C. The particle size of the conductive filler is minus 140 mesh to minus 325 mesh; D. The mass ratio of the polyethylene glycol to the polyaniline is 1:(8-15).

3. A method for preparing the conductive filler according to claim 1 or 2, characterized in that: include: The polyethylene glycol, the polyaniline and the organic solvent are first mixed to obtain a conductive copolymer mixed solution; The conductive copolymer mixed solution and the nickel-coated graphite powder are subjected to fluidized bed coating and drying to obtain the conductive filler.

4. The method for preparing the conductive filler according to claim 3, characterized in that: At least one of the following conditions is met: A. Under a reducing atmosphere, the nickel-coated graphite powder is pretreated to obtain treated nickel-coated graphite powder, and the treated nickel-coated graphite powder is subjected to fluidized bed coating; B. The concentration of the conductive copolymer mixed solution is 2%-5.5%.

5. The method for preparing the conductive filler according to claim 4, characterized in that: At least one of the following conditions is met: A. The gas in the reducing atmosphere includes hydrogen; B. The pretreatment temperature is 500°C-600°C, and the insulation time is 1h-4h.

6. The method for preparing the conductive filler according to claim 3, characterized in that: The fluidized bed coating comprises: The nickel-coated graphite powder is dispersed; The conductive copolymer mixed solution is sprayed on the surface of the dispersed nickel-coated graphite powder.

7. The method for preparing the conductive filler according to claim 6, characterized in that: At least one of the following conditions is met: A. The dispersed air inlet temperature is 90°C-110°C; B. The dispersed air inlet pressure is 1.0 bar-1.5 bar; C. The dispersed air flow rate is 5m 3 / h-10m 3 / h; D. The spray pressure of the spraying is 0.7 bar-1.5 bar; E. The spraying speed of the spraying is 50mL / min-80mL / min; F. The atomization time of the spraying is 5min-10min.

8. The method for preparing the conductive filler according to claim 3, characterized in that: The drying temperature is 100° C.-120° C., and the drying time is 2 h-4 h.

9. A conductive adhesive, characterized in that: The conductive filler comprises the conductive filler according to claim 1 or 2 or the conductive filler prepared by the preparation method of the conductive filler according to any one of claims 3 to 8.

10. An electronic device, characterized in that: Including the conductive adhesive as claimed in claim 9.